Modulation of active Ca2+ uptake by the islet-cell endoplasmic reticulum. - Colca, J R (1983)
The possible effects of calmodulin and cyclic AMP on active Ca2+ uptake by the islet-cell endoplasmic reticulum were investigated. Neither calmodulin nor cyclic AMP affected the rate of active Ca2+ uptake, or the steady-state filling capacity of the endoplasmic reticulum when measured in the absence of oxalate. Consistent with these results, calmodulin did not activate the Ca2+-stimulated ATPase activity associated with this cell fraction. During the course of these experiments., it was unexpectedly discovered that the rate of Ca2+ uptake, as well as the steady-state Ca2+ filling capacity of the endoplasmic reticulum, were markedly increased by unidentified factor(s) in the cytosol. This effect could be demonstrated by reconstitution of the membranes in cytosol, or by direct addition of fresh or dialysed cytosol to the Ca2+ uptake assays. The degree of activation by the cytosol indicates that the endoplasmic reticulum may play a prominent role in controlling beta-cell Ca2+ concentrations and that the unidentified activator(s) present in the cytosol may be involved in regulation of this function.